Describing ionising radiation risk in the clinical setting: A systematic review. Issue 1 (February 2019) - Younger, C.W.E.; Wagner, M.J.; Douglas, C.; Warren-Forward, H.
Abstract: Introduction: Meaningfully explaining the risk of an ionising radiation examination is a challenging undertaking. Patients must contextualise the risk against the expected benefit of the imaging examination, often in a situation of heightened emotion. This systematic review seeks to explore the literature to identify what techniques are advocated for disclosing the risk to patients of ionising radiation from clinical medical imaging examinations. Methods: A systematic review of peer-reviewed literature was undertaken. Electronic databases were searched to identify peer-reviewed, full-text articles published in English from 1990. Original articles discussing techniques for disclosing ionising radiation risks in the clinical setting were included. The reference lists of the included articles were searched for unpublished articles and reports of use. Results: Sixteen papers out of 5959 unique titles met the inclusion criteria. The data was extracted independently by two researchers and assessed for quality using the Joanna Briggs Institute critical appraisal tools. Conclusion: The two most commonly cited techniques for disclosing ionising radiation risk is to compare risk to the risk of common life events, and to describe risk as an additive risk to the baseline risk of cancer. The most commonly cited communication strategy was a graphical representation of the data, but simple language is also advocated. The use of a pictograph represents a technique which satisfied the advocated techniques of most articles. Highlights: There is little contemporary research into how best to disclose clinical ionising radiation risk. A standardised method of radiation risk disclosure would aid patients understanding of risk. Literacy, numeracy and radiation jargon represent barriers to effective communication of risk. Pictography may represent the most-advocated ionising risk disclosure technique.